BUDAYA SEKOLAH MULTIKULTUR - Andreana Kusumaningtyas (Jurnal Manajemen Pendidikan, 2014)
In order to have a new different point of view in facing differences, schools are encouraged to start implementing the concept of multicultural education. One of the schools is Sekolah Highscope Indonesia Tb. Simatupang. As a multicultural school, this school provides its members with school culture components. They are: (1). Values. The four core values this school promotes are: Respect, Responsibility, Integrity and Excellence. (2). Folkways/ Habit. One of them is to use language of the day, English or Indonesia as one of way to accommodate and building team works between school members. (3). Norms. The use of norms can see on how school members follow rules created by the school. (4). Symbol. The utilizes of symbols needs more improvement since many of school members don’t have enough understanding about the concepts of symbol itself. All components of school culture are addressed to help school members behave better.